Cannabinoids Recent Perspectives and Applications in Human Health - James, Steven P. (IntechOpen, 2023)
Cannabinoids - Recent Perspectives and Applications in Human Health presents the latest research on cannabinoids for human health, covering topics such as potential emerging therapeutic applications and safety concerns. Not only does this book provide an up-to-date source of information for physicians and scientists, but it also provides insight into the wide range of potential applications for cannabinoids in health care. With this new publication, the medical community will gain a more comprehensive understanding of cannabinoids and their potential applications in human health. This book is an invaluable resource for both physicians and scientists alike.